“MEMBAGI DUNIA”: CARA PENGELOLAAN MODAL SOSIAL PURA DI DENPASAR - I Nyoman Yoga Segara (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
This study aims to reveal the creative ways that pengempon and traditional village boards develop and manage collective capital in the temples of Denpasar. In the past, capital in the form of temples only meant pelaba and pratima, but now a variety of assets have been developed. To empower the pengempon, officials of the traditional village manage it by combining traditional and modern management methods to increase the total quality of management. They are of the opinion that temples may have productive assets to meet its secular needs in the realm of the socio-cultural and the economic. This can be done because they conceptually and clearly “divide the world”–in other words, they divide capital into two worlds: sekala and niskala. Capital is divided according to the structure of the temple as hierarchically conceived by Tri Mandala. This conception opens up space to manage assets based on the framework of Tri Hita Karana. The divided world of nista-madya-mandala is a real illustration of the journey from the concrete to the abstract world.